A new blind snake (Serpentes: Typhlopidae) from an endangered habitat in south-eastern Queensland, Australia - Venchi, Alberto; Wilson, Steve K.; Borsboom, Adrian C. (Zootaxa, 2015)
A new species of blind snake is described from south-eastern Queensland, eastern Australia. Anilios insperatus sp. nov. differs from all of its congeners in having:16 scales around the body; 442 paravertebral scales; snout slightly trilobed from above and bluntly angular in profile; small, inconspicuous eyes, located within the ocular scale at its junction with the preocular and the supraocular scales; and uniform light colouration. The unique specimen was collected from pasture that was formally Queensland regional ecosystem 12.8.24, a eucalypt dominated ecosystem currently listed as endangered. The site is less than 100 km from Queensland’s capital, Brisbane. Given the locality, habitat and absence of additional specimens, the species is probably of conservation concern.